MODEL PENGAMBILAN KEPUTUSAN DESENTRALISASI PADA UNIT LEMBAGA KEUANGAN - Komala Ardiyani; M Maulidin Fachrur (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2012)
This  study aims  to  determine the model  of decentralized    decisions on unit financial institutions and decentralized decision model differences between banks and non-banks. The decision-making in the expansion areas include marketing, determination of new assets, sales and hiring priorities. Research  data obtained  by sending questionnaires  to the  respondents. The  respondents of  this study is  the unit managers of  financial  institutions.  Forty-eight  (48) questionnaires were used in data  processing.  The  data is  processed using different  test t-test.  These  results  prove that  the decentralized decision n occurs when the unit is to expand new market areas and prioritize sales, while other decisions in the hands of central management. The results of different test t-test states that  there  are differences between  the decentralized decision  model two  types  of financial institutions.Keywords: Decisiondecentralization, financial institutionsunit.